Initial romanian experience with green light hps 120 w laser in bph - P., Geavlete (J Med Life, 2008)
Introduction and objectives:Potassium-titanyl-phosphate (KTP) laser photoselective vaporization prostatectomy (PVP) is a relatively new technology for the management of benign prostatic hyperplasia (BPH). We reviewed our initial experience regarding the efficacy and safety of this technique for symptomatic and obstructive BPH. Material and methods: During the last year, 35 patients with a mean age of 65.3 years (between 53 and 80) and symptomatic BPH were treated by laser prostatectomy using KTP/532 laser energy at 120W. The procedure was performed through a 21F continuous-flow cystoscope with normal saline as irrigant. All patients underwent standard urologic evaluation using the International Prostate Symptom Score (IPSS), the urinary peak flow rate (Qmax), ultrasound measurement of prostate volume and residual urine volume, assay of prostate specific antigen (PSA) and digital rectal examination (DRE). The mean prostatic volume was 45cm3 (range 30–70cm3). The patients were reassessed postoperatively at 3 and 6 months. Results: In all cases, KTP laser vaporization was successfully performed, with a mean operating time of 57 minutes (range 20-120 minutes). In most cases, we used just one fibre, the mean energy released being 170.000 Joules (range 80.000-270.000). The mean hospital stay was 24 hours. No major complications occurred intraoperatively or postoperatively, and no transfusions were necessary. All patients were catheter-free after 1 month. At 3 and 6 months, the mean urinary peak flow increased from the preoperative value of 8.5mL/sec to 23.7mL/sec and 21.2mL/sec, respectively. The mean IPSS decreased from 19.0 to 9.5 and 7.5 at 3 and 6 months, and the mean post-voiding residual volume (PVR) decreased from 90.5 to 30.5mL and 15.0 mL. Two patients were admitted for secondary hematuria and urinary infection, and 7 patients presented irritative low urinary tract symptoms during their first postoperative check-up. Conclusions: BPH photoselective vaporization using 120W Green Light laser is a safe and easy to learn technique, with good functional results and a low rate of complications.